2019
DOI: 10.1136/tsaco-2019-000318
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on severity of solid organ injury in the adult population at a Level I trauma center

Abstract: BackgroundThe obese (body mass index, BMI > 30) have been identified as a subgroup of patients in regards to traumatic injuries. A recent study found that high-grade hepatic injuries were more common in obese than non-obese pediatric patients. This study seeks to evaluate whether similar differences exist in the adult population and examine differences in operative versus non-operative management between the obese and non-obese in blunt abdominal trauma.MethodsPatient with trauma evaluated at an American Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…It is defined as a BMI ≥ 30 kg/m 2 by adopting National Institutes of Health (NIH) and World Health Organization (WHO) guidelines [3,4]. It has been widely discussed in the trauma literature Healthcare 2021, 9, 1006 2 of 11 and studies have shown that obesity is associated with a higher risk for post-trauma complications and mortality [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as a BMI ≥ 30 kg/m 2 by adopting National Institutes of Health (NIH) and World Health Organization (WHO) guidelines [3,4]. It has been widely discussed in the trauma literature Healthcare 2021, 9, 1006 2 of 11 and studies have shown that obesity is associated with a higher risk for post-trauma complications and mortality [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The higher obesity grade the smaller percent of the instrumental diagnostic approaches reliability in such patients. This causes the necessity of more frequent implementation of the invasive methods, which, on the one hand improved the injuries verification, and on the other -provoked the risks of complications connected both with their implementation and intervention into the body cavities [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…The scope of medical aid for the traumatized at the pre-hospital stage depended upon the subjective assessment of the patients' general condition by the emergency team. Polytraumatized patients were diagnosed and treated at hospital according to the common and local protocols, which included the collection and analysis of the complaints, medical history and features of the traumatizing factor [1,2,10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A.K. Chen et al found an increase in the frequency of interventions and mortality in patients with liver injury with increased BMI [6], while C.Y. Fu et al, in contrast, found that obesity reduced the incidence of blunt abdominal trauma and operations due to damage of the abdominal organs [7].…”
Section: Introductionmentioning
confidence: 99%